Phrasal Verbs in The Jakarta Post: Types and Functions in Media Discourse - Dimas Alif Muhammad; Muhammad Kiki Wardana; Emmy Erwina (Talenta Publisher, 2026)
This study investigates the types and functions of phrasal verbs in five selected articles from The Jakarta Post, published between August and December 2024. A qualitative descriptive approach was applied, following Miles and Huberman’s interactive model of analysis: data collection, data reduction, data display, and conclusion drawing. The theoretical framework combines Michael Lewis’s Lexical Approach (1993) with classifications of phrasal verbs into transitive, intransitive, separable, inseparable, literal, and figurative categories. Data were drawn from online newspaper articles, while secondary data consisted of books, journals, and prior studies on phrasal verbs. The findings reveal a dominance of figurative and inseparable phrasal verbs across all articles, highlighting their vital role in journalistic discourse. These verbs simplify complex issues, enhance stylistic impact, and make articles accessible to general readers. The study suggests pedagogical implications for English language teaching, particularly in integrating phrasal verbs into classroom instruction, and calls for further research on phrasal verb usage in broader journalistic and literary contexts.